PEMBUATAN KEMASAN UNTUK MENINGKATKAN NILAI JUAL PEMASARAN PRODUK PADA UMKM SASIA - Nawawi, M. Tony; Darryl; Bravo, Christiandinata Tjandra (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The purpose of the activity is to provide assistance in making seasoning product packaging owned by MSMEs in an effort to help improve the marketing of local Indonesian MSME products. The activity will be applied to the owner of the Sasia brand seasoning MSME production business domiciled in Tangerang, considering that partners still really need product packaging assistance for better marketing. Sasia MSME partners were chosen due to the weak selling value of the packaging provided to consumers, lack of knowledge, and not having better product packaging options that can provide added value to the seasoning products to be sold. This condition is due to the limited working capital owned by partners. So that the product packaging is not maximized. The method offered in the activity is to provide knowledge of the selling value of product packaging, assistance in making product design and packaging. Through this activity, the team will help Sasia MSME product entrepreneurs to do business more oriented towards increasing the selling value of product marketing to consumers through packaging that is not inferior to competitors. Which in turn will lead to an increase in consumer interest in purchasing Sasia brand seasoning products owned by partners.